PENENTUAN NILAI CBR DAN NILAI PENYUSUTAN TANAH TIMBUNAN (JALAN RUAS TAIS-MARAS KABUPATEN BENGKULU SELATAN) - Muhamad Zen Zen; James Hellyward (Universitas Bengkulu, 2024)
In civil engineering, soil plays a crucial role as it supports the strength of the construction above it.. Thus, research was conducted on native soil in the Tais-Maras region of South Bengkulu Regency. Testing was carried out to determine the properties of the native soil intended for construction activities, including water content according to SNI 03-1965:2008, specific gravity according to SNI 03-1964:2008, plastic limit according to SNI 03-1966:2008, liquid limit according to SNI 03-1967:2008, hydrometer analysis according to SNI 03-3423:2008, activity value, CBR according to SNI 03-1744-1989, and shrinkage limit research according to SNI 03-1996-1990. Based on research and data calculation from disturbed soil samples in the Tais-Maras region of South Bengkulu Regency, the soil properties were determined as follows: water content (W) 98.52%, specific gravity (Gs) 2.415, liquid limit (LL) 45%, plastic limit (PL) 33.85%, Plasticity Index (PI) 11.2%, Optimum Moisture Content (OMC) 34.9%, dry density 1.120 Kg/Cm3, and a CBR design value of 3.9%. The calculated shrinkage limit value was 38%, and the soil activity value was 2.6. It can be concluded that this soil belongs to the OL category, with 'O' representing organic silt due to the hydrometer analysis showing particle sizes ranging from 0.002 mm to 0.0074 mm with high plasticity and moisture content, thus indicating that it is unsuitable for bearing construction loads.